Risk Factor Prevalence of Late Onset Preeclampsia in Dr. Soetomo General Hospital Surabaya - Fajrinka Pralampito; Agus Sulistyono; Sri Purwaningsih (Faculty of Medicine Universitas Airlangga, 2021)
Introduction: Preeclampsia is a condition of hypertension that occurs after 20 weeks of gestation, followed by the detection of protein in the urine sample, and is one of the major causes of maternal mortality. It is categorized, based on time of gestation, into 2-stage are early and late-onset. One of the more accessible tools in diagnosing and also preventing preeclampsia is by its risk factors. The aim of this study was to observe the appearance of some of the risk factors in patients with late-onset preeclampsia and to allow a better approach in patients with said comorbidities.Methods: This was a descriptive observational study. The sample used was 35 patients diagnosed with late-onset preeclampsia in Dr. Soetomo General Hospital Surabaya from January to December 2016.Results: Among 35 patients diagnosed with late-onset preeclampsia, obesity (65.71%) appeared the most. Maternal age (37.15%) and primigravida (28.57%) appeared in second and third places. Chronic hypertension appeared only in 6 (17.14%) patients, whereas multiple pregnancies appeared in 3 (8.57%). Both patients with a history of previous preeclampsia and diabetes mellitus only appeared once (2.86%).Conclusion: Obesity has the most appearance in patients with late-onset preeclampsia, followed by maternal age and primigravida.